Implementation of the Village Revenue and Expenditure Budget Policy (APBDes) in Infrastructure Development in 2019 (Study in Tiambang Village, Pematang Tiga District, Central Bengkulu Regency) - Herdiyansyah Herdiyansyah; Yusuarsono Yusuarsono; Antonio Imanda (Penerbit Jurnal Indonesia, 2022)
The purpose of this study is the Implementation of Village Income and Expenditure Budget (APBDes) on Infrastructure Development in 2019 (in Tiambang Village, Pematang Tiga Sub-District, Central Bengkulu Regency). This research is categorized as descriptive qualitative using data collection methods of interviews, observation and documentation. The selection of informants by purposive sampling consisted of seven people using the theory of the principles of APBDes according to Edi Suharto, (2010: 80). Siding with community groups, in making village physical development plans not all village communities are involved and development planning decisions still depend on the village head. Transparent, budget preparation and accountability financial reports for the physical development of village communities do not get accountability reports for development results. can be accounted for, the accountability report and the amount of the village physical development budget is accepted by the community but is not comprehensive. Participation, the community does not participate in the implementation of village physical development because they are only representatives of groups in the community. Democracy, in the physical development process of the village head is always open to receiving suggestions from the village community. Sustainable, Development in the village is budgeted annually in relation to the interests of the village community. Effective, project development runs on time according to the target to be achieved. Efficient, the development carried out by Tiambang village government has been maximized due to visible economic and social changes.